Membangun Literasi Baca-Tulis Yang Menyenangkan Dengan Penggunaan Multimedia Di SDN 066043 Medan Helvetia - Andre Oktavanus; Gusti Pirandy (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Multimedia in Reading-Writing Literacy in Elementary Schools is a learning aid that is used to display, present, present, or explain lesson material to students. With the increasing variety of types and quality of learning media, teachers need to be more selective in choosing learning media. Reading and writing are activities that are always considered boring by students, especially elementary school children. There are several problems encountered in the field related to learning, namely the student's assumption that Reading-Writing Literacy is boring. Moreover, in their learning, the average teacher uses conventional methods, thus making learning seem monotonous, rigid and dominated by the teacher. The solution offered in this Practicum activity is to utilize existing school Multimedia, such as the use of infocus media, and YouTube learning animations that are expected to create a creative, innovative, and fun learning atmosphere in schools, and have a positive impact on UPT SDN 066043 Medan Helvetia so that expectations learning is achieved. This practicum uses the CaseWork method proposed by Zastrow, as follows: Intake and contract, Assessment, Planning, Intervention, Evaluation, Termination. The results of this practicum activity aim that the children at SDN 066043 Medan Helvetia can understand learning easily and have fun.